Peningkatan Hasil Belajar Ilmu Pengetahuan Alam Peserta Didik Melalui Media Model Dengan Metode Inkuiri Di Kelas V SD Negeri 04 Payakumbuh Tahun 2019/2020 - Vivi Rezkia (Departement of Mathematics Education, 2021)
This study aims to improve student learning outcomes in class VC SD Negeri 04 Payakumbuh through a media model using the inquiry method. This type of research is classroom action research (CAR). The subjects of this study were all VC class students of SD Negeri 04 Payakumbuh in the 2019/2020 school year, totaling 35 people. The data obtained comes from student data, teachers, and documentation. The data collection procedure used observation instruments, field notes, tests, and documentation. The results showed that the media model with the inquiry method could improve student learning outcomes in science subjects for class VC SD Negeri 04 Payakumbuh. This is evidenced by the average value from the initial conditions of 62, in the first cycle it rose to 68.57, in the second cycle it became 76.28 and in the third cycle it reached 84.